Learn Computer Science with Swift Computation Concepts, Programming Paradigms, Data Management, and Modern Component Architectures with Swift and Playgrounds - Feiler, Jesse (Apress, 2018)
Master the basics of solving logic puzzles, and creating algorithms using Swift on Apple platforms. This book is based on the curriculum currently being used in common computer classes. You'll learn to automate algorithmic processes that scale using Swift in the context of iOS, macOS, tvOS, and watchOS. Begin by understanding how to think computationally: to formulate a computational problem and recognize patterns and ways to validate it. Then jump ahead past the abstractions and conceptual work into using code snippets to build frameworks and write code using Xcode and Swift. Once you have frameworks in place, you'll learn to use algorithms and structure data. Finally, you'll see how to bring people into what you've built through a useable UI and how UI and code relate.